Preparation of high-precision CO2 with known triple oxygen isotope for oxygen isotope analysis. Issue 5 (3rd September 2021) - Sha, Lijuan; Mahata, Sasadhar; Duan, Pengzhen; Zong, Baoyun; Ning, Youfeng; Zhang, Pu; Wang, Jian; Cai, Yanjun; Cheng, Hai
ABSTRACT: The objective of this work is to propose a more effective way to prepare an in-house CO2 with known triple oxygen isotope compositions. The major experimental steps include: (1) the O2 is combusted to CO2 on a graphite rod at 750 °C with Pt-catalyst for 3–4 min; and (2) converted CO2 is subsequently purified by two cryogenic traps. The results show high reproducibility of δ 13 C and δ 18 O values of the converted CO2 within 0.010–0.020 ‰ and 0.006–0.010 ‰ (1 σ, SD), and the identical δ 18 O value within error with that of the original O2 . Additionally, we have measured the triple oxygen isotope compositions of converted CO2 using an O2 –CO2 Pt-catalyzed oxygen-isotope equilibration method. The measured δ 17 O values of CO2 show high reproducibility within 0.006 ‰ (1 σ, SD), and are identical within error with the original O2 as well. Notably, our experiments also found that the O2 with heavier oxygen isotope ratios ( δ 18 O > 40 ‰, VSMOW) might have a lesser conversion efficiency, and this effect, combined with the lighter isotope preferential fractionations during the reaction processes of O2 to CO and CO to CO2, may explain the observed lower 17 O/ 16 O and 18 O/ 16 O ratios of the converted CO2 relative to the original O2 .